(untitled) (Contemporary Journal of Social Science Review, 2025)
This study aims to analyze how Pakistani English newspapers, specifically Dawn and The Express Tribune, use language to construct and represent social and cultural realities. It reflects on which linguistic features are used to depict social and cultural issues, how these features frame narratives, and how newspaper language mirrors Pakistan’s social and cultural context. Using a qualitative research design with textual analysis, this research examines editorials and headlines that were published over two months using Halliday’s Systemic Functional Linguistics (SFL) framework. The analysis focuses on linguistic features such as transitivity, modality, evaluation, and thematic organization to uncover how these elements frame social narratives, highlight power relations, and convey ideological viewpoints. The results indicate that while relational, mental, and linguistic processes convey perception, characterization, and opinion, material processes still predominate in event representation. By combining factual reporting with critical remarks, interpersonal choices such as modality and declarative mood help readers understand social and political issues. The lack of behavioral processes emphasizes a formal and impersonal reporting tone. Coherence is ensured, and reader engagement is increased by textual organization using rheme and thematic patterns. The study shows how language elements in Pakistani newspapers influence cultural understanding, transmit ideology, and create social meaning. By emphasizing how language shapes public perception, this study advances media linguistics and lays the groundwork for further research on linguistic representation and ideological production in Pakistani media.